Effective and durable genetic modification of human mesenchymal stem cells via controlled release of rAAV vectors from self-assembling peptide hydrogels with a maintained differentiation potency. (May 2015) - Rey-Rico, Ana; Venkatesan, Jagadeesh K.; Frisch, Janina; Schmitt, Gertrud; Monge-Marcet, Amália; Lopez-Chicon, Patricia; Mata, Alvaro; Semino, Carlos; Madry, Henning; Cucchiarini, Magali
Graphical abstract: Abstract: Controlling the release of recombinant adeno-associated virus (rAAV) vectors from biocompatible materials is a novel, attractive approach to increase the residence time and effectiveness of a gene carrier at a defined target site. Self-assembling peptides have an ability to form stable hydrogels and encapsulate cells upon exposure to physiological pH and ionic strength. Here, we examined the capacity of the peptide hydrogel RAD16-I in a pure (RAD) form or combined with hyaluronic acid (RAD-HA) to release rAAV vectors as a means to genetically modify primary human bone marrow-derived mesenchymal stem cells (hMSCs), a potent source of cells for regenerative medicine. Specifically, we demonstrate the ability of the systems to efficiently encapsulate and release rAAV vectors in a sustained, controlled manner for the effective transduction of hMSCs (up to 80%) without deleterious effects on cell viability (up to 100%) or on their potential for chondrogenic differentiation over time (up to 21 days). The present study demonstrates that RAD16-I is an advantageous material with tunable properties to control the release of rAAV vectors as a promising tool to develop new, improved therapeutic approaches for tissue engineering in vivo .